2012
DOI: 10.1007/s00360-012-0652-0
|View full text |Cite
|
Sign up to set email alerts
|

Coping with physiological oxidative stress: a review of antioxidant strategies in seals

Abstract: While diving, seals are exposed to apnea-induced hypoxemia and repetitive cycles of ischemia/reperfusion. While on land, seals experience sleep apnea, as well as prolonged periods of food and water deprivation. Prolonged fasting, sleep apnea, hypoxemia and ischemia/reperfusion increase oxidant production and oxidative stress in terrestrial mammals. In seals, however, neither prolonged fasting nor apnea-induced hypoxemia or ischemia/reperfusion increase systemic or local oxidative damage. The strategies seals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 111 publications
3
54
1
Order By: Relevance
“…While the role UCP2 plays in regulating cellular metabolism is not well defined, decreased hepatic UCP2 is associated with impaired lipid metabolism and antioxidant capacity in insulin-resistant rats (Montez et al, 2012). Because we have demonstrated that insulin resistance develops with fasting duration in elephant seal pups (Viscarra et al, 2011a;Viscarra et al, 2011b;Viscarra et al, 2012), but with enhanced lipid metabolism and antioxidant capacity (Vázquez-Medina et al, 2011;Vázquez-Medina et al, 2012), the observed increase in UCP2 may contribute to the regulation of both lipid metabolism and oxidative stress in late-fasted pups. Collectively, the increases in the genes measured indicate that fasting duration is associated with upregulation of the TH-mediated signal transduction pathway in adipose and muscle in a select group of mammals uniquely adapted to periods of extensive food deprivation.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…While the role UCP2 plays in regulating cellular metabolism is not well defined, decreased hepatic UCP2 is associated with impaired lipid metabolism and antioxidant capacity in insulin-resistant rats (Montez et al, 2012). Because we have demonstrated that insulin resistance develops with fasting duration in elephant seal pups (Viscarra et al, 2011a;Viscarra et al, 2011b;Viscarra et al, 2012), but with enhanced lipid metabolism and antioxidant capacity (Vázquez-Medina et al, 2011;Vázquez-Medina et al, 2012), the observed increase in UCP2 may contribute to the regulation of both lipid metabolism and oxidative stress in late-fasted pups. Collectively, the increases in the genes measured indicate that fasting duration is associated with upregulation of the TH-mediated signal transduction pathway in adipose and muscle in a select group of mammals uniquely adapted to periods of extensive food deprivation.…”
mentioning
confidence: 72%
“…Because our hypothesis focused on the changes in the deiodinases and the TH receptor, these proteins were given priority. Protein expression was quantified by standard western blot as previously described (Vázquez-Medina et al, 2011;Viscarra et al, 2011a;Viscarra et al, 2011b;Vázquez-Medina et al, 2012;Soñanez-Organis et al, 2012;Viscarra et al, 2012). The primary antibodies for DI1 and DI2, THrβ1, TATA binding protein, histone H3 and β-actin (Santa Cruz Biotechnology, Santa Cruz, CA) were diluted 1:500 to 1:5000.…”
Section: Quantification Of Protein Expression By Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Diving ability is enhanced by cardiovascular adjustments such as bradycardia (lower heart rate) and peripheral vasoconstriction (Vázquez-Medina et al 2012), while angiogenesis contributes to the maximal oxygen consumption in skeletal muscle capillarity (Gavin et al 2007). Thus, the HIF-1α-induced VEGF expression may contribute to the adaptation of diving species to either aerobic or anaerobic metabolism during breath-hold diving.…”
Section: Discussionmentioning
confidence: 99%